2013
DOI: 10.1097/scs.0b013e3182a15dfc
|View full text |Cite
|
Sign up to set email alerts
|

Study Comparing Midazolam and Nitrous Oxide in Dental Anxiety Control

Abstract: The purpose of this study is to comparatively assess the effect of midazolam and nitrous oxide associated with oxygen, in lower third molar extractions, on the change in the anxiety level of patients by salivary cortisol dosage. Twenty-eight male patients underwent lower third molar extraction under sedation with midazolam and nitrous oxide. Objective (salivary cortisol dosage) and subjective (Corah Dental Anxiety Scale) data have been obtained. By salivary cortisol, 40 minutes after midazolam administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 13 publications
2
24
0
6
Order By: Relevance
“…Midazolam has become the standard drug because it is an ideal sedative for this type of surgical procedure. Its short action is consistent with the average duration of a dental procedure (5-7,13-18). However, contrary to most authors, Zanette et al (19) concluded in their work that diazepam would be better than midazolam in conscious sedation dentistry.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Midazolam has become the standard drug because it is an ideal sedative for this type of surgical procedure. Its short action is consistent with the average duration of a dental procedure (5-7,13-18). However, contrary to most authors, Zanette et al (19) concluded in their work that diazepam would be better than midazolam in conscious sedation dentistry.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, sedation with benzodiazepines requires that patients be accompanied to appointments with the recommendation not to operate motor vehicles or hazardous machinery for the duration of the drug’s pharmacological effects. Among the benzodiazepines, midazolam is most commonly used for sedation during dental treatments (5-7). …”
Section: Introductionmentioning
confidence: 99%
“…The surgical procedures were performed in twenty-five healthy outpatients (52 % females) between 18 and 25 years of age using the split-mouth design. This kind of randomized clinical trial has been used in oral health research, comprising each of two treatments are randomly assigned to either the right or left halves of the patient, decreasing the bias of familiarity with the surgery (Pereira-Santos et al, 2013;Lesaffre et al, 2009). The attractiveness of this design is that it removes a lot of inter-individual variability from the estimates of the treatment effect (Lesaffre et al).…”
Section: Discussionmentioning
confidence: 99%
“…Corah’s Dental Anxiety Scale (DAS) [24], which is commonly used to assess dental anxiety [2528], was administered as a third questionnaire to measure patient dental anxiety. The scale consists of 4 questions, each with 5 answer alternatives.…”
Section: Methodsmentioning
confidence: 99%